Review of Facing Trauma in Contemporary American Literary Discourse (American & British Studies Annual, 2020)
Review of Facing Trauma in Contemporary American Literary Discourse: Stories of Survival and Possibility by Laura Virginia Castor. Newcastle: Cambridge Scholars, 2019. 213 p. ISBN 978-1-5275-3813-9